Re: How to simplify hypergeometrics
- To: mathgroup at smc.vnet.net
- Subject: [mg128404] Re: How to simplify hypergeometrics
- From: "Dr. Wolfgang Hintze" <weh at snafu.de>
- Date: Sat, 13 Oct 2012 01:04:19 -0400 (EDT)
- Delivered-to: l-mathgroup@mail-archive0.wolfram.com
- Delivered-to: l-mathgroup@wolfram.com
- Delivered-to: mathgroup-newout@smc.vnet.net
- Delivered-to: mathgroup-newsend@smc.vnet.net
- References: <k55o3n$e7q$1@smc.vnet.net> <k586hh$is3$1@smc.vnet.net>
On 12 Okt., 06:34, Roland Franzius <roland.franz... at uos.de> wrote: > Am 11.10.2012 08:14, schrieb Dr. Wolfgang Hintze: > > > > > > > Consider the probability function > > > p[n_, a_, b_, k_] := > > Binomial[k - 1, a - 1]*(Binomial[n - k, b - a]/Binomial[n, b]) /; {0 > > <= a <= > > b, n >= a} > > > In[68]:= p[n, a, b, k] > > > Out[68]= (Binomial[-1 + k, -1 + a]*Binomial[-k + n, -a + b])/ > > Binomial[n, b] > > > Now let's look for the zeroeth moment k^0 (for the higher ones the > > situation is similar) > > > In[69]:= k0 = Sum[p[n, a, b, k], {k, 1, n}] > > > Out[69]= ((-Binomial[-1, -a + b])*Binomial[n, -1 + a]* > > Hypergeometric2F1[1 - a + b, 1 + n, 2 - a + n, 1] + > > Binomial[0, -1 + a]*Binomial[-1 + n, -a + b]* > > HypergeometricPFQ[{1, 1, 1 - a + b - n}, {2 - a, 1 - n}, 1])/ > > Binomial[n, b] > > > This should give 1, but it looks clumsy. > > All general expression with HypergeometricPFQ generally will be wrong > for integer parameters in the numerator parameters. > > One has to regularize by extracting and cancelling infinite Gamma > factors at negative integers but that means to have control of the > evaluation by understanding the limit formulas. > > Contrary to your assumption of a normalized ditribution the direct > conversion > > Binomial[n_,k_]:> Pochhammer[n-k+1,k]/k! leaves you with the expression > > p[n_, a_, b_, k_]:=(b! Pochhammer[1 - a + k, -1 + a] Pochhammer[ > 1 + a - b - k + n, -a + b])/((-1 + a)! (-a + b)! Pochhammer[ > 1 - b + n, b]) > > Simplify[Sum[p[6, a, b, k], {k, 0, n}]] /. {n->6 ,a -> 1, b -> 3} > > is not independent of a,b,n > > Perhaps a normalization constant is missing? In any binomial > distribution the normalized distribution has to contain n-th powers of > the parameters > > -- > > Roland Franzius Hello Roland, thank you for your reply. 1) I extract your idea to use Pochhammer to convert the original distribution (which IS normalized, contrary to your statement) p[n_, a_, b_, k_] := Binomial[k - 1, a - 1]*(Binomial[n - k, b - a]/Binomial[n, b]) to this form pp[n_, a_, b_, k_] := (b!*Pochhammer[1 - a + k, -1 + a]* Pochhammer[1 + a - b - k + n, -a + b])/ ((-1 + a)!*(-a + b)!*Pochhammer[1 - b + n, b]) Comparing the two expressions for concrete values, also checking the nomalization: Table[p[10, 3, 4, k], {k, 1, 10}] Plus @@ % {0, 0, 1/30, 3/35, 1/7, 4/21, 3/14, 1/5, 2/15, 0} 1 Table[pp[10, 3, 4, k], {k, 1, 10}] Plus @@ % {0, 0, 1/30, 3/35, 1/7, 4/21, 3/14, 1/5, 2/15, 0} 1 2a) Ok, so now we calculate again the zeroeth moment of k (which should give 1, of course). But, the result does not contain 2F1 anymore but is something (DifferenceRoot) which I have never seen before, and is not easily recognized as being = 1 k0 = Sum[pp[n, a, b, k], {k, 1, n}] (1/(Gamma[a]*Gamma[1 - a + b]*Gamma[1 + n]))*(Gamma[1 + b]*Gamma[1 - b + n]* DifferenceRoot[ Function[{\[FormalY], \[FormalN]}, {(-\[FormalN])*(-\[FormalN] + a - b + n)*\[FormalY][\[FormalN]] + (-\[FormalN] - 2*\[FormalN]^2 + 2*\[FormalN]*a - \[FormalN]*b + n + 2*\[FormalN]*n - a*n)* \[FormalY][ 1 + \[FormalN]] + (-1 - \[FormalN] + a)*(-\[FormalN] + n)*\[FormalY][2 + \[FormalN]] == 0, \[FormalY][1] == 0, \[FormalY][2] == Gamma[n]/(Gamma[2 - a]*Gamma[a - b + n])}]][ 1 + n]) 2b) Trying now to simplify with all information about the parameters gives ... FullSimplify[k0, {Element[{n, a, b}, Integers], Inequality[0, Less, a, LessEqual, b], n >= a}] FullSimplify::infd:Expression Gamma[1+b] Gamma[1-b+n] DifferenceRoot[Function[{\[FormalY],\[FormalN]},{-\[FormalN] Plus[<<4>>] \[FormalY][<<1>>]+Plus[<<7>>] \[FormalY][<<1>>] +Plus[<<3>>] Plus[<<2>>] \[FormalY][<<1>>]==0,\[FormalY][1]==0,\ [FormalY][2]==Gamma[n]/(Gamma[<<1>>] Gamma[<<1>>])}]][1+n] simplified to Indeterminate. >> FullSimplify::infd:Expression (1/(Gamma[a] Gamma[1-a+b] Gamma[1+n]))Gamma[1+b] Gamma[1-b+n] DifferenceRoot[Function[{\ [FormalY],\[FormalN]},{-\[FormalN] Plus[<<4>>] \[FormalY][<<1>>] +Plus[<<7>>] \[FormalY][<<1>>]+Plus[<<3>>] Plus[<<2>>] \[FormalY] [<<1>>]==0,\[FormalY][1]==0,\[FormalY][2]==Gamma[n]/(Gamma[<<1>>] Gamma[<<1>>])}]][1+n] simplified to Indeterminate. >> Indeterminate 3a) So telling Mathematica in advance everything known about the parameters, gives no evaluation at all Assuming[{Element[{n, a, b, k}, Integers], Inequality[0, Less, a, LessEqual, b], n >= a, 1 <= k <= n}, k0 = Sum[pp[n, a, b, k], {k, 1, n}]] Sum[(b!*Pochhammer[1 - a + k, -1 + a]* Pochhammer[1 + a - b - k + n, -a + b])/((-1 + a)!*(-a + b)!* Pochhammer[1 - b + n, b]), {k, 1, n}] 3b) Putting Assuming under the sum k0 = Sum[Assuming[{Element[{n, a, b, k}, Integers], Inequality[0, Less, a, LessEqual, b], n >= a, 1 <= k <= n}, pp[n, a, b, k]], {k, 1, n}] (1/(Gamma[a]*Gamma[1 - a + b]*Gamma[1 + n]))*(Gamma[1 + b]*Gamma[1 - b + n]* DifferenceRoot[ Function[{\[FormalY], \[FormalN]}, {(-\[FormalN])*(-\[FormalN] + a - b + n)*\[FormalY][\[FormalN]] + (-\[FormalN] - 2*\[FormalN]^2 + 2*\[FormalN]*a - \[FormalN]*b + n + 2*\[FormalN]*n - a*n)* \[FormalY][ 1 + \[FormalN]] + (-1 - \[FormalN] + a)*(-\[FormalN] + n)*\[FormalY][2 + \[FormalN]] == 0, \[FormalY][1] == 0, \[FormalY][2] == Gamma[n]/(Gamma[2 - a]*Gamma[a - b + n])}]][ 1 + n]) gives us back the expression of attempt 2a). 4) Fixing n in advance results in a funny thing like this one FullSimplify[ With[{n = 10}, Assuming[{Element[{n, a, b, k}, Integers], Inequality[0, Less, a, LessEqual, b], n >= a, 1 <= k <= n}, k0 = Sum[pp[n, a, b, k], {k, 1, n}]]]] (1440*b!*((28*(19 + 8*a - 9*b))/(Gamma[11 - a]*Gamma[2 + a - b]) + (214 + 3*a^2 + a*(5 - 4*b) + b*(-41 + 3*b))/ (Gamma[8 - a]* Gamma[6 + a - b]) + (7/((-8 + a)*(-7 + a)*(-6 + a)*(-5 + a)*Gamma[3 + a - b]) + (12600 + a*(-7435 + (2305 - 228*a)*a) - 1385*b - 23*(-5 + a)*a*b + 2*(50 + a)*b^2 - 3*b^3)/Gamma[10 + a - b])/ Gamma[5 - a]))/ ((-a + b)!*Gamma[a]*Pochhammer[11 - b, b]) In summary: I didn't get the desired result and need more help. Regards, Wolfgang